Recurrent myopericarditis as a complication of Marijuana use - Rodríguez-Castro, Carlos E. (International Scientific Literature, Inc., 2014)
Patient: Male, 29 Final Diagnosis: Myopericarditis Symptoms: Chest pain Medication: Ibuprofen Clinical Procedure: — Specialty: Cardiology OBJECTIVE: Unusual clinical course BACKGROUND: Cannabis is the most commonly used illegal substance worldwide and its consumption portends significant side effects. Nowadays, in order to increase its psychotropic effect, various substances are being added constantly to it to promote its potency that might hold toxic effects to different organs including the heart and might lead to other unreported complications such as myopericarditis. Herein, we are presenting a unique case of recurrent myopericarditis after the consumption of contaminated marijuana, an association that has not been reported in literature before. CASE REPORT: A 29-year-old man presented to our institution with pressure-like left-sided chest pain that is aggravated by cough and deep inspiration and relieved by sitting and leaning forward. Examination revealed pericardial rub and workup showed elevated white blood cell count, C-reactive protein and troponin I level of 2.99 ng/ml. ECG upon admission showed ST-segment elevation in the inferior leads with PR-segment depression. Echocardiogram revealed only concentric hypertrophy. Patient was admitted to another institution with similar symptoms 2 months earlier. Patient admitted to using adulterated Marijuana on both occasions prior to hospitalization. Review of medical records from the outside hospital revealed similar ECG and laboratory findings. Treatment with Ibuprofen resulted in resolution of patient’s symptoms and ECG abnormalities. CONCLUSIONS: Recurrent myopericarditis in our patient is likely the result of consumption of contaminated Marijuana. Careful history taking in patients presenting with myopericarditis is crucial as it might be the causal link.